Peran Brand Image dalam Memediasi Pengaruh Celebrity Endorser Terhadap Niat Beli - Darma Putra, I Ketut Triya; Sulistyawati, Eka (E-Jurnal Manajemen, 2015)
Abstract Topics covered in this study is how the influence of celebrity endorser and brand image on purchase intention Nike Kobe basketball shoes and how the role of brand image in mediating influence on purchase intention of celebrity endorser Nike Kobe basketball shoes. Total respondents were 110 respondents using purposive sampling technique. Data obtained by distributing questionnaires that measured with Likert scale and analyzed using path analysis (path analysis) to determine the direct effect of variable celebrity endorser of the brand image, variable celebrity endorser on purchase intention and brand image of the variable purchase intention. This study also accompanied by Sobel test to determine the effect of indirect variable in mediating the effects of brand image on purchase intention of celebrity endorser. The results of this study indicate that the celebrity endorser significant positive effect on brand image, celebrity endorser significant positive effect on purchase intention, brand image significant positive effect on purchase intention and brand image mediate the effect of celebrity endorser that impact increased intention to buy the product. So it can be concluded that the celebrity endorser and brand image can affect purchase intentions Nike Kobe basketball shoes. Keywords: celebrity endorser, brand image, purchase intention